2011
DOI: 10.1007/s12603-010-0278-4
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and functional correlates of nutrition among community-dwelling older adults in Ireland

Abstract: The results emphasise the importance of mobility and social supports in mediating nutritional outcomes in Irish community-dwelling older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 28 publications
(19 reference statements)
1
33
0
Order By: Relevance
“…The odds for malnutrition was increased by 1.6 among older adults considered as socially isolated based on the LSNS 6. Similar findings were published by Romero‐Ortuno et al ., who showed, within a sample of 556 Irish community dwellers aged 65 years and older, that perceived social support assessed through the LSNS 6 was one of the strongest predictors of malnutrition . Furthermore, among a sample of more than 4000 older individuals from 11 European countries, limited social activities were related to a twofold higher risk for weight loss during the previous month .…”
Section: Discussionmentioning
confidence: 92%
“…The odds for malnutrition was increased by 1.6 among older adults considered as socially isolated based on the LSNS 6. Similar findings were published by Romero‐Ortuno et al ., who showed, within a sample of 556 Irish community dwellers aged 65 years and older, that perceived social support assessed through the LSNS 6 was one of the strongest predictors of malnutrition . Furthermore, among a sample of more than 4000 older individuals from 11 European countries, limited social activities were related to a twofold higher risk for weight loss during the previous month .…”
Section: Discussionmentioning
confidence: 92%
“…23 There are three versions of the scale that assess combinations of both the frequency and quality of family, friendship and neighbour ties. Cross-sectional studies using the LSNS have demonstrated associations between more social connections and a lower incidence of major depressive disorder in Chinese 24,25 and Singaporean older adults, 26 less depressive symptoms among older adults in Hong Kong 27 and Macau, 24 increased 33 In a prospective cohort study of 7240 community-dwelling older women in the US, the odds of experiencing increasing and persistently high depressive symptoms over 20 years were significantly elevated for women who had fewer social connections (odds ratios (OR) 3.24 and 6.75 respectively). 34 A prospective study examining the risk of falls in a group of older Caucasian women in the US identified that more connections with family members protected older women against falls.…”
Section: Social Connectionsmentioning
confidence: 99%
“…Furthermore, social isolation and loneliness are associated with chronic health conditions, cognitive impairment, poor self-reported health, and sleep disorders [30, 31]. Older adults who experience these psychosocial determinants are more likely to eat alone and often have chronically marginal nutrient intake, putting them at a greater risk for malnutrition [32]. Of particular concern are widowed or single older men.…”
Section: Nutritional Vulnerability In the Communitymentioning
confidence: 99%